Iodine, Cyanide, Thyroid Stimulating Hormone and Free Thyroxine Levels - Khatimah, Husnul; Fandir, Abdul; Rahmawati, Reny; Hardianti, Andi; Amin, Nur Afia (PT FORMOSA CENDEKIA GLOBAL, 2025)
Nutrients that play an important role in the formation of thyroxin (T4, pro-hormone) and triiodotironim (T3, the active hormone) which are elements of the formation of thyroid hormone in thyroid follicle cells are iodine. However, iodine absorption is affected by goitrogen, one of which is cyanide. This study is an observational analytical study with a Cross Sectional design on 50 hyperthyroid patients undergoing treatment at the Magelang Health Research and Development Center. Intake data was obtained by the 2x24-hour recall method while TSH and FT4 data were obtained from laboratory examinations conducted at the Magelang Health Research Institute. The results showed that there was a relationship between iodine intake and TSH levels of hyperthyroid patients (p<0.05). Meanwhile, iodine intake with FT4 levels was not significant (p=0.319). There is a meaningful relationship between iodine intake and TSH levels of hyperthyroid patients.